Comparative analysis of intermittent exercise training with and without blood flow restriction on physiological and performance matric / Amirul Shamsuddin ... [et al.]. - Shamsuddin, Amirul; Linoby, Adam; Mior, Zafyrah; Mohd Dan, Azwa Suraya; Kamalden, Tengku-Fadilah; Lisbôa, Felipe Domingos (2024)
This study tested the hypothesis that intermittent exercise training (IET) combined with blood flow restriction (BFR) would improve muscle oxygen saturation (SmO2) and exercise performance. We investigated the effects of 6 weeks (3 days per week) of intermittent exercise training combined with BFR on the high-intensity intermittent exercise performance, SmO2, blood [glucose], and rating of discomfort. Following completion of a baseline Yo-Yo intermittent recovery level 1 test (Yo-Yo IR1), twenty-eight young men recreationally active in endurance-based sports were pair-matched and randomly assigned to the IET-BFR and IET-only groups. The IET-BFR group performed IET (50% of the maximum distance covered in Yo-Yo IR1 at baseline in 5 sets) with inflatable cuffs (1.3 × resting systolic blood pressure), and the IET-only group performed the same training without inflatable cuffs. Performance in the Yo-Yo IR1 was 8.3% greater (p < 0.05) with IET-BFR (1,444 ± 319 m) compared to IET-only (1,330 ± 362 m) after 18 training sessions. Additionally, the IET-BFR group exhibited significantly higher post-training SmO2% during the Yo-Yo IR1 test (p < 0.05). There were no significant differences between groups in blood [glucose] or rating of discomfort. These findings suggest that incorporating BFR into IET protocols could effectively enhance exercise performance, potentially attenuating the decline in local oxygen delivery.